Tax Burden and Bonus Mechanisms on Transfer Pricing With Tunneling Incentive as a Moderating Variable - Tina Lestari; Jumriaty Jusman (Syntax Corporation Indonesia, 2025)
This study aims to investigate the effect of tax burden and bonus mechanism on transfer pricing with incentive tunneling as a moderation variable. The population of this study consists of multinational manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. Samples were selected using purposive sampling, with a total of 52 samples with an outlier of 13 data from the total. So the amount of data that will be used in this study is 39 samples. Data analysis methods include the Chow test, the Hausman test, and Moderate Regression Analysis (MRA). This study shows that tax burdens and bonus mechanisms have an influence on transfer pricing. The moderation variable of incentive tunneling cannot strengthen the influence of tax burden on transfer pricing. The moderation variable of incentive tunneling can strengthen the positive influence of the bonus mechanism on transfer pricing. The research provides relevant practical guidelines for corporate managers, investors, and policymakers. The main implication is the need for a more holistic approach in managing transfer pricing that balances the goals of tax optimization, performance motivation, and adherence to good corporate governance principles.